Pengaruh Likuiditas, Profibilitas, dan Pertumbuhan Penjualan Terhadap Kebijakan Dividen (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Fatchur Rohman; Zulia Safitri (Jurnal Rekognisi Akuntansi, 2019)
The background of this problem is due to fluctuations in the distribution of dividend policies or those proxied by an unstable dividend payout ratio, while investors want a stable dividend policy and the differences in the results of previous studies that make researchers want to do research. This study aims to determine the effect of Liquidity, Profitability, and Sales Growth on Dividend Policy in Consumer Goods Industrial Sector Companies Listed on the Indonesia Stock Exchange. The data used in this study are documentary data in the form of Liquidity, Profitability, Sales Growth, and Dividend Policy obtained from financial reports from the official website www.IDX.co.id. The number of samples used was 14 companies that met the criteria and were listed on the IDX in 2013-2017. Data analysis was performed using a multiple linear regression test. The results of this study indicate that: 1) liquidity has no and no significant effect on dividend policy, 2) profitability has no and no significant effect on dividend policy, 3) sales growth has no and no significant effect on dividend policy, 4) liquidity, profitability, and Sales growth together has no effect on dividend policy.